Reconstructing The Philosophy Of Education Based On Humanism: Returning To Human Nature In The Learning Process - Dirman Dirman (Oasis : Jurnal Ilmiah Kajian Islam, 2025)
This research aims to examine the relationship between philosophy, humans, and education as a theoretical foundation in building an educational system capable of transforming social and intellectual life. The main problem raised in this research is how philosophical principles about human nature can be integrated into the educational paradigm so as to produce pedagogical practices that are humanist, critical, and transformative. This research uses a qualitative approach through descriptive-analytical library research. Data sources were obtained from classical and contemporary philosophy literature, as well as modern educational theories relevant to the themes of humanism, existentialism, and educational emancipation. The results show that philosophy provides a reflective and normative framework for education in understanding humans as intelligent, moral, and social beings. When education is carried out with a strong philosophical foundation, it is able to create a learning space that not only develops cognition, but also the ethical and social awareness of students. Thus, education is no longer understood in a purely technocratic manner, but as a means of forming a whole person and reconstructing civilization. This article recommends the integration of philosophical approaches in the curriculum and educational practices as a strategy to build a just, inclusive and value-oriented society.